2020
DOI: 10.1371/journal.pntd.0008293
|View full text |Cite
|
Sign up to set email alerts
|

Unusual dominant genotype NIA1 of Enterocytozoon bieneusi in children in Southern Xinjiang, China

Abstract: Enterocytozoon bieneusi is the mainly pathologies or intestinal disorders that causes approximately 90% of reported cases of human microsporidiosis. To understand the prevalence and genotype distribution of E. bieneusi in the Xinjiang Uygur Autonomous Region, China, 609 fecal samples were collected from children in kindergarten in Southern Xinjiang and screened for this pathogen by PCR and sequencing of the internal transcribed spacer (ITS). Thirty-six fecal samples (5.9%, 36/609) were positive for E. bieneusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The infection of E. bieneusi was 4.2% (29/683) and 5.7% (39/683) in HIV-negative patients and HIV-positive patients in Henan province [12], respectively. Additionally, the following rates of infection were observed in other studies on other regions in China: 1.18% (27/2284) in children in Zhengzhou [13], 5.9% (36/609) in Xinjiang [14], 2.5% (3/121) in Daqing [15], 0.2% (1/500) in children in Wuhan [16], 13.49% (34/252) in adults and children of a diarrhea clinic in Shanghai [17], 11.83% (11/93) in children in Chongqing [18], and 11.58% (33/285) in HIV-positive patients in Guangxi [19]. According to statistics, the prevalence of E. bieneusi is 6.4% in southern China, and 5.5% in northern China [11], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The infection of E. bieneusi was 4.2% (29/683) and 5.7% (39/683) in HIV-negative patients and HIV-positive patients in Henan province [12], respectively. Additionally, the following rates of infection were observed in other studies on other regions in China: 1.18% (27/2284) in children in Zhengzhou [13], 5.9% (36/609) in Xinjiang [14], 2.5% (3/121) in Daqing [15], 0.2% (1/500) in children in Wuhan [16], 13.49% (34/252) in adults and children of a diarrhea clinic in Shanghai [17], 11.83% (11/93) in children in Chongqing [18], and 11.58% (33/285) in HIV-positive patients in Guangxi [19]. According to statistics, the prevalence of E. bieneusi is 6.4% in southern China, and 5.5% in northern China [11], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 68%
“…More than 470 genotypes have been identified by this method in humans, mammals, birds, and water, including 59 human-specific and 31 zoonotic genotypes. In China, there are 41 genotypes (including genotype D, I, J, CHN1, CHN2, CHN3, CHN4, EbpC, type IV, Peru8, Peru11, PigEBITS7, Henan-I, Henan-II, Henan-III, Henan-IV, Henan-V, CS-4, NEC1, NEC2, NEC3, NEC4, NEC5, GX25, GX456, GX458, CQH1, CQH2, CQH3, CQH4, A, CHN6, EbpA, KB-1, NIA1, CXJH1, CXJH2, CXJH3, J, BEB6, and CM8) that have been identified in humans [9,[12][13][14][15][16][17][18][19]. Phylogenetic analysis of the ITS sequence revealed the presence of at least 11 different genetic clusters, named as Groups 1 to 11 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Diverse infection rates of the pathogen were observed in children in different studies across the world (Table 1S). For example, as seen in our study, similar prevalence of the pathogenic infection was reported in kindergarten children (5.9%, 36/609) in China (Qi et al., 2020), liver transplant children (6.8%, 3/44) in Iran (Agholi et al., 2013), children aged 0–2 years (8.2%, 29/354) (Rogawski et al., 2018) and 6–23 months (9.5%, 88/928) (Platts‐Mills et al., 2017) in Bangladesh, and children (9.7%, 7/72) in Nigeria (Maikai et al., 2012). The higher prevalence was documented in leukemic children (29.0%, 29/100) in Egypt (Shehab et al., 2020), children with persistent diarrhea (30.4%, 68/224) in Uganda (Mor et al., 2009), and HIV‐infected children (37.1%, 13/35) in Malawi (Huibers et al., 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, previous studies have reported the presence of four other genotypes (Type IV, Peru6, D, and Henan-III) in humans and animals around the world, of which genotypes D and Type IV are commonly found in E. bieneusiinduced microsporidiosis in humans [3,28]. Both genotypes D and Type IV have been detected in infants, HIV-positive patients, and HIV-negative patients in China [25,[29][30][31][32][33]. Meanwhile, they have been found in NHPs, pigs, dogs, snakes, cats, hippopotamus, Pere David's deer, chinchillas, Siberian tiger, lions, Fischer's lovebird, red foxes, wastewater, and lake water [3].…”
Section: Discussionmentioning
confidence: 99%